1992
DOI: 10.1152/ajprenal.1992.262.5.f807
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporters of rat proximal tubule: differential expression and subcellular distribution

Abstract: In the late proximal tubule, glucose reabsorption progressively lowers the concentration of luminal glucose, and concentrative glucose influx increases to ensure complete glucose reabsorption. The change in glucose influx is effected by luminal Na(+)-dependent glucose transporters (Na(+)-GLUT), which exhibit higher Na(+)-to-glucose stoichiometric ratios in the late proximal tubule. In this work, the corresponding changes in the axial distribution of basolateral glucose efflux transporters (GLUTs) were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 0 publications
4
34
0
1
Order By: Relevance
“…Our studies have shown that the mesangial cell Na+-coupled glucose transporter has close similarities to the carrier from epithelial cells in regard to its specificity of response to the Na + ion, capacity to promote the uptake of (z-methyl-glucoside and inhibition by phlorizin [9,19,21,[24][25][26]. The size of the co-transporte r transcript in the rat mesangial cells (2.2 kb) is similar not only to that of LLC-PK1 cells [21] but also to that reported for rat kidney cortex SGLT1 [29,30]. Furthermore its K m value is comparable to that observed in oocytes after injection of SGLT1 cRNA together with the cRNA of membrane-associated protein (RS1) from porcine kidney [31].…”
Section: Discussionsupporting
confidence: 59%
“…Our studies have shown that the mesangial cell Na+-coupled glucose transporter has close similarities to the carrier from epithelial cells in regard to its specificity of response to the Na + ion, capacity to promote the uptake of (z-methyl-glucoside and inhibition by phlorizin [9,19,21,[24][25][26]. The size of the co-transporte r transcript in the rat mesangial cells (2.2 kb) is similar not only to that of LLC-PK1 cells [21] but also to that reported for rat kidney cortex SGLT1 [29,30]. Furthermore its K m value is comparable to that observed in oocytes after injection of SGLT1 cRNA together with the cRNA of membrane-associated protein (RS1) from porcine kidney [31].…”
Section: Discussionsupporting
confidence: 59%
“…Quantitation of the bands revealed that BLM levels of GLUT1 were 78. 6 30.0 a.u. ), although the increase only reached statistical significance after 21 days (p < 0.02 compared to control) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Although the protein is found in certain transporting cells e.g. renal proximal tubule and Caco-2 cells [6,7], there is, to date, no evidence for its expression in normal small intestinal epithelium [8]. In the present study we have used confocal immunofluorescence microscopy of rat jejunum, together with Western blotting of BBM and BLM prepared from intestinal mucosa, in order to examine the normal enterocyte distribution of *Corresponding author.…”
Section: Animalsmentioning
confidence: 99%
“…In the early S1 segment, where the bulk of filtered glucose is reabsorbed, the low affinity/ high capacity glucose transporters, SGLT2 and GLUT2 are co-expressed in the luminal brush border membrane and in the basolateral membrane, respectively. Increases in the cortical GLUT2 gene expression have been extensively reported in diabetes (9)(10)(11)(12)(13)(14)(15), and are important for renal glucose reabsorption maintenance in this condition, since high blood and interstitial glucose concentrations may lower the outwardly directed glucose gradient from tubule to blood (11). GLUT1 protein is also detected in the outer renal cortex, where it is not related to the tubule epithelial cells, but to the mesangial cells (16).…”
Section: Introductionmentioning
confidence: 99%